1996
DOI: 10.1128/mcb.16.9.5147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Nuclear Export Signal of Human T-Cell Lymphotropic Virus Type 1 Rex Reveals that Nuclear Export Is Mediated by Position-Variable Hydrophobic Interactions

Abstract: The Rex protein of human T-cell lymphotropic virus type 1 (HTLV-1) mediates the cytoplasmic localization of incompletely spliced and unspliced viral RNAs (24). Rex is a member of a family of functionally related proteins, generally known as the Rev-like proteins, which are found in complex retroviruses. The Rev-like proteins have at least two essential domains with unique functions, (i) a specific RNA binding activity that interacts with structural response elements within the viral mRNAs and (ii) an effector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 29 publications
4
103
0
Order By: Relevance
“…They also demonstrated that endogenous zyxin actually shuttles between the cytoplasm and nucleus. Ajuba also contains a strong putative NES, in a region of the protein complementary to the site of the NES present in zyxin (7,21). Interestingly, when we removed the pre-LIM domain of Ajuba, including a putative NES, and expressed this LIM-only isoform of Ajuba in fibroblast cells, we observed that a significant proportion of the LIM-only Ajuba was now present in the nucleus.…”
Section: Discussionmentioning
confidence: 73%
“…They also demonstrated that endogenous zyxin actually shuttles between the cytoplasm and nucleus. Ajuba also contains a strong putative NES, in a region of the protein complementary to the site of the NES present in zyxin (7,21). Interestingly, when we removed the pre-LIM domain of Ajuba, including a putative NES, and expressed this LIM-only isoform of Ajuba in fibroblast cells, we observed that a significant proportion of the LIM-only Ajuba was now present in the nucleus.…”
Section: Discussionmentioning
confidence: 73%
“…The NES-like sequence, composed of 3-5 hydrophobic amino acids with defined spacing (Bogerd et al, 1996;Kim et al, 1996), probably mediates the macromolecular traffic between the nucleus and cytoplasm. The nuclear export receptor Xpo1/CRM1 (Kudo et al, 1997) mediates the nuclear export of leucine-rich NES-containing proteins by binding directly to the NES (Fornerod et al, 1997;Fukuda et al, 1997;Stade et al, 1997).…”
Section: Tristetraprolinmentioning
confidence: 99%
“…Regions which map to amino acids 57 ± 66 and 106 ± 124 were suggested to mediate Rex oligomerization (Bogerd and Greene, 1993;Weichselbraun et al, 1992a). A leucine-rich nuclear export signal (NES), identi®ed between amino acids 79 and 99, is essential for nucleo-cytoplasmic tra cking and thus Rex function (Bogerd et al, 1996;Kim et al, 1996;Palmeri and Malim, 1996;Weichselbraun et al, 1992b). Factors reported to interact directly with the NES domain include the eukaryotic initiation factor 5A (eIF-5A) (Katahira et al, 1995) and the export factor CRM1 (Fornerod et al, 1997;Fukuda et al, 1997;Ossareh-Nazari et al, 1997;Stade et al, 1997).…”
Section: Introductionmentioning
confidence: 99%